Building in the Past: A Preliminary Analysis of the Construction Materials and Methods Used in Structure A in Barangay Pinagbayanan, San Juan, Batangas - Sales, Angelus Maria P. (Hukay; Vol 18, 2013)
The Batangas Field School Program under its field director, Grace Barretto-Tesoro, has been excavating Structure A, Site I in Barangay Pinagbayanan, San Juan, Batangas for two consecutive years. In 2009, the southern portion of Structure A was investigated which resulted to the discovery of parts of an old Spanish house more commonly known as bahay na bato. This Spanish house is believed to be made up of adobe blocks and wooden sidings with capiz windows and clay roof tiles. In 2010, the focus shifted from the southern portion of Structure A to its northern portion. The results from the 2010 excavation became a vital source of additional information about the whole structure. With the whole of Structure A almost excavated, a study of the construction technology employed to create the house should be done to further understand the structure. This paper will attempt to make such study. This paper will discuss the construction materials and technology used to build Structure A and compare it with other archaeologically investigated Spanish colonial structures. An overview of the transition from nipa huts to stone houses with respect to the changes in their construction techniques will also be given. Finally, recommendations will be given with respect to conducting an archaeological research that deals with structures.